EFFECT OF CYCLODEXTRINS ON PROTEIN-BINDING OF DRUGS - THE DIFLUNISAL HYDROXYPROPYL-BETA-CYCLODEXTRIN MODEL CASE - Sideris, EE; Koupparis, MA; Macheras, PE (PHARMACEUTICAL RESEARCH, 1994)
The binding of diflunisal to hydroxypropyl-beta-cyclodextrin (HPbetaCD), bovine serum albumin (BSA), human serum albumin (HSA), normal human plasma, and mixed solutions of HPbetaCD/protein was studied at 25-degrees-C, pH 7.4, by potentiometry using an electrode selective to diflunisal. The experimental data for diflunisal/HPbetaCD fit well to the 1:1 binding model. The binding of diflunisal with each of the studied proteins was compatible with a model having two independent classes of binding sites. The binding of diflunisal in mixed solutions HPbetaCD/BSA, HPbetaCD/HSA, and HPbetaCD/plasma increased considerably when the HPbetaCD concentration was increased. The binding behavior of the two biomolecules in the mixed solutions of HPbetaCD/BSA or HPbetaCD/HSA was described with an `'additive'' model formulated on the basis of the estimates of the binding parameters of diflunisal derived from the separate experiments with each one of the binders tested. The lower than theoretical binding observed in HPbetaCD/plasma solutions was ascribed to the competitive displacement of diflunisal from the HPbetaCD cavity by plasma cholesterol.
Keywords: diflunisal; hydroxypropyl-beta-cyclodextrin; ion-selective electrodes; Protein Binding